Capitalism and communism [videorecording] - The Center for Humanities ([S.l.] Makati The Associated Press Felta [manufacturer], 1987)
Identifies the basic conflict between the United States and Soviet Union. Compares and contrasts the communist and capitalist systems. Explains why many countries in the 1980's turned to the free enterprise system instead of its economic counterpart in communist countries.
Pt.1. Comparisons and contracts (9 min.) -- Pt.2. Communism: how it works -- Pt.3. Capitalism: how it works -- Pt.4. Struggles (7 min.)
VHS.
Keywords: Capitalism; Communism; Marxian economics; ECONOMICS; BUSINESS; HISTORY